The 2016 Red Tide Crisis in Southern Chile: Possible Influence of the Mass Oceanic Dumping of Dead Salmons - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
In 2016, a massive harmful algal bloom (HAB) of Alexandrium catenella around Chiloe island caused one of the major socio-ecological crisis in Chilean history. This red tide occurred in two distinct pulses, the second, most anomalous, bursting with extreme toxicity on the Pacific coast, weeks after the highly controversial dumping off Chiloe of 4,700 t of rotting salmons, killed by a previous HAB of Pseudochattonella verruculosa. We study the transport of this pollution, analyzing the physical oceanographic conditions during and after the dumping. We find that a cyclonic gyre was present between the dumping site and the coast, visible in satellite altimetry and sea surface temperature data. Using Lagrangian simulations, we confirm that near-surface currents could have brought part of the pollution to the coast, and fueled the bloom. This scenario explains also the anomalous later finding of ammonium near Chiloe. Finally we discuss the mismanagement of risk throughout the events.